Development of an integrated demand-supply balancing system for supply chain exception handling. (1st January 2014) - Wang, Li-Chih; Cheng, Chen-Yang
Most enterprises are suffering information invisibility in multi-site production supply chain information. Without appropriate information transparency, supply chain exception such as due date changes, and material shortage usually increase the planning complexity. In addition, the balance of supply and demand for each distinct manufacturing site simultaneously is quite difficult to maintain. Therefore, this study develops an integrated demand-supply balancing (IDSB) system framework and takes a textile company that has implemented the IDSB system to demonstrate how the IDSB system to handle supply chain exception. DSB function justifies the feasibility of each reallocation plan in terms of supply and demand balancing perspective. Finally, a textile company case study shows that the IDSB system can indeed support global production planners to effectively generate more feasible multi-site master production schedule and reallocation plan than traditional approach in terms of available material, capacity and order due date.